Nonconstant Periodic Solutions of Discrete p-Laplacian System via Clark Duality and Computations of the Critical Groups - Bo Zheng (Abstract and Applied Analysis)
We study the existence of periodic solutions to a discrete p-Laplacian system. By using the Clark duality method and computing the critical groups, we find a simple condition that is sufficient to ensure the existence of nonconstant periodic solutions to the system.